Quality assessment of beef burgers packaged in active paper with cinnamon essential oil - PINTO, Laura Adriane de Moraes; NASCIMENTO, Karina Favoreto; CARDOSO, Melina Aparecida Plastina; MADRONA, Grasiele Scaramal; SCAPIM, Mônica Regina da Silva; VITAL, Ana Carolina Pelaes; GUERRERO, Ana; PRADO, Ivanor Nunes do (Food Science and Technology, 2023)
The aim of this study was to evaluate a new packaging system in which the paper was covered with a solution of sodium alginate and cinnamon essential oil (CEO) that was used as packaging for burger beef. The papers were characterized for their physical, optical, mechanical, and sorption properties. In addition, the burgers were evaluated for their antioxidant activity, lipid oxidation, and color difference. In total, four treatments were developed: Con: paper without coating; Pad: paper with alginate coating; Pco 0.1: paper with alginate coating added with 0.1% CEO; and Pco 0.05: paper with alginate coating added with 0.05% CEO. The analysis of the thickness showed the effectiveness in the formation of the film coating, which was confirmed by the analysis of morphology. The results indicated that the coating had no improvement in mechanical properties nor in water vapor permeability (WVP); however, color changes were noted (P<0.002). The sorption isotherms showed that the equilibrium was not modified for the coated papers. All samples showed an increase in the value of malonaldehyde during storage (P<0.003) and a decrease in antioxidant activity (P<0.001). However, in papers containing CEO, these modifications were lower when compared to Pad and Con. In addition, the samples containing CEO presented a lower color difference (P<0.002).